2012
DOI: 10.2176/nmc.52.470
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation for the Treatment of Abnormal Posture and Gait Disorder in Patients With Parkinson's Disease

Abstract: Patients with advanced Parkinson's disease (PD) often present with axial symptoms, including abnormal posture, postural instability, and gait disorder. Although spinal cord stimulation (SCS) is effective for pain, little is known about the effect of SCS on motor function in PD patients. The present study investigated the effect of SCS on posture and gait in 15 PD patients, 5 men and 10 women aged 63-79 years (mean 71.1 years), with low back pain and leg pain who received SCS. A visual analog scale (VAS) was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 27 publications
3
85
0
Order By: Relevance
“…Although the patient reported by our group was> 70 years of age, he had an excellent response to levodopa with limited axial motor impairment. Similarly, in the study by Agari and Date [16] the patients displayed limited axial symptoms without any major gait abnormalities. Patients in the 2 other reports [18,19] were younger (43 and 68 years old, respectively), but their clinical characteristics were less precisely described.…”
Section: Human Studiesmentioning
confidence: 53%
See 3 more Smart Citations
“…Although the patient reported by our group was> 70 years of age, he had an excellent response to levodopa with limited axial motor impairment. Similarly, in the study by Agari and Date [16] the patients displayed limited axial symptoms without any major gait abnormalities. Patients in the 2 other reports [18,19] were younger (43 and 68 years old, respectively), but their clinical characteristics were less precisely described.…”
Section: Human Studiesmentioning
confidence: 53%
“…Additionally, a 43-year-old woman with PD who benefited from stimulation at the C2 level for neck and upper extremity neurogenic pain displayed a 40 % improvement in the motor UPDRS-III score following SCS [15]. A larger Japanese study of 15 patients with PD suffering from neuropathic pain and treated with thoracic SCS using percutaneous leads showed some improvement in PD symptoms [16]. Because pain localization [12], which concluded a lack of clinical benefit, the 2 patients were>70 years old, had advanced disease with poor levodopa responsiveness, and 1 had severe gait abnormalities.…”
Section: Human Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…In PD, a similar approach using spinal cord stimulation (SCS) has been tested for the purpose of interfering with synchronized low-frequency oscillations characteristic of the parkinsonian state. Good results were initially achieved in rodent models of PD (Fuentes et al, 2009), and more recently, clinically validated effects have also been reported ( Agari and Date, 2012;F é nelon et al, 2012;Hassan et al, 2013; see also Nicolelis et al, 2010). In the treatment of levodopa-induced dyskinesia, however, stimulation of afferent pathways remains to be evaluated.…”
Section: Breaking the Waves -A Neuromodulatory Approachmentioning
confidence: 99%